Previously unpublished Odonata records from Sarawak, Borneo, part VI: Miri Division including checklists for Niah, Lambir Hills, Loagan Bunut and Pulong Tau National Parks - Dow, Rory A.; Rambli, Ahmad; Butler, Stephen G.; Choong, Chee Yen; Jongkar, Grinang; Ng, Yong Foo; Ngiam, Robin W.J.; Reels, Graham T.; Steinhoff, P.O.M.; Joanes, Unggang (International Dragonfly Fund, 2021)
Recods of Odonata made from 2005 to 2020 in Miri Division in Sarawak are presented, including records from Lambir Hills, Loagan Bunut, Niah and Pulong Tau National Parks. Primary types of Odonata originating from Miri Division are listed. Surveys of more than one day duration in Miri Division and covered here are tabulated with the funding source where appropriate; four of the surveys covered here were funded by the International Dragonfly Fund. One hundred and eighty-eight species are listed based on surveys made by the authors, of which Macromia jucunda Lieftinck, 1955, had not been recorded from Borneo before, Burmagomphus arthuri Lieftinck, 1953 is a new record for Miri Division and Camacinia gigantea (Brauer, 1867) has only been recorded from the Division re-cently with the only published record in a difficult to access publication (Choong (2020)). At least 48 more of the species listed were recorded from Miri Division for the first time in surveys covered in this report, although the records have been published (in most cases with no details beyond division and district in Dow (2021)) before. Two forms of Xiphi-agrion cyanomelas Selys, 1876 are recorded and the likelihood that they represent different species is discussed. A possibly new, large sized, species of Macromia allied to M. westwoodii Selys, 1874 is recorded and discussed. Other notable records not published with details before include Rhinocypha stygia Förster, 1897, Rhinoneura caerulea Kimmins, 1936, Dysphaea lugens (Selys, 1873), Euphaea ameeka van Tol & Norma-Rashid, 1995, Euphaea basalis (Laidlaw, 1915), Amphicnemis new sp. cf mariae Lieftinck, 1940 (previously recorded from Usun Apau National Park), Anaciaeschna jaspidea (Burmeister, 1839), Heliaeschna uninervulata Martin, 1909, Borneogomphus sp., Heliogomphus borneensis Lieftinck, 1964, Ictinogomphus acutus (Laidlaw, 1914), Chlorogomphus sp., Macromia corycia Laidlaw, 1922, Idionyx montana Karsch, 1891, Hylaeothemis clementia Ris, 1909, Orchithemis xanthosoma Laidlaw, 1911, Rhyothemis fulgens Kirby, 1889, Rhyothemis regia (Brauer, 1867), Tetrathemis sp. cf platyptera Selys, 1878, Tramea phaeoneura Lieftinck, 1953 and Tramea sp. cf virginia (Rambur, 1842). The habitat preferences of Dysphaea lugens are discussed. A male-male tandem of Coeliccia nigrohamata Laidlaw, 1918 is reported. The somewhat peculiar distribution of Argiocnemis rubescens rubeola Selys, 1877 and Pseudothemis jorina Förster, 1904 in Sarawak is discussed. Activity of the apparently normally crepuscular Heliaeschna uninervulata in the middle of the day is reported. An interesting morphological detail of some female Chlorogomphus from Sarawak is discussed. The likelihood that Macromia corycia is a junior synonym of M. gerstaeckeri Krüger, 1899 is discussed. The possibility that the range of Rhyothemis regia is expanding in Sarawak is remarked upon. The identity of Tramea sp. cf virginia is discussed. With the records presented here at least 222 species of Odonata are known from Miri Division and with the addition of Macromia jucunda to the known fauna, 309 species have now been recorded from Sarawak. More detailed specimen records are given in Appendix 1 and a revised checklist of Odonata from Lambir Hills National Park and the first checklis from Loagan Bunut, Niah and Pulong Tau National Parks are given in Appendix 2.